Descending necrotizing mediastinitis complicating hyperimmunoglobulin E syndrome. Issue 4 (16th May 2016) - Takanashi, Yusuke; Hayakawa, Takamitsu; Neyatani, Hiroshi; Funai, Kazuhito
Abstract: Descending necrotizing mediastinitis (DNM) is a potentially lethal disease that originates from a deep neck infection (DNI); it is often associated with an immunocompromised state. Hyperimmunoglobulin E syndrome (HIES) is an extremely rare complex immune deficiency characterized by recurrent abscesses of staphylococcal etiology. A rare case of a 34‐year‐old woman wherein HIES putatively promoted the development of DNI into DNM is described. She presented with cervical purulent lymphadenitis and retropharyngeal abscess. Despite immediate cervical drainage and use of broad‐spectrum antibiotics, she developed DNI and subsequently DNM. Mediastinal drainage with thoracotomy and subsequent deep neck drainage were performed. Bacterial culture of the abscess isolated methicillin‐resistant Staphylococcus aureus (MRSA). Although a postoperative recurrent deep neck abscess required a second surgery, we succeeded in conservative remission of recurrent mediastinal abscess with long‐term use of anti‐MRSA drugs. Sufficient drainage under thoracotomy and robust administration of postoperative antibiotics resulted in successful management of HIES‐associated DNM. Abstract : A rare case of a 34‐year‐old woman wherein hyperimmunoglobulin E syndrome (HIES) putatively promoted the development of deep neck infection into descending necrotizing mediastinitis (DNM) is described. Sufficient drainage under thoracotomy and robust administration of postoperative antibiotics resulted in successful management of HIES‐associated DNM.